Hidup Sehat Bersama Yoga - Dwitayasa, I Made (JURNAL YOGA DAN KESEHATAN, 2018)
Yoga is an archaeological discovery at the time of culture in the city of Harappa and Mahenjadaro, which is embodied in a statue of Lord Shiva and Goddess Parvati who was doing a variety of different asanas, where there is a belief that Lord Shiva is a yoga teacher while Goddess Parvati is a student. Maharsi Patanjali in the Yoga known as Raja Yoga or yoga Astangga with eight members, namely Yama, Nyama, Asana, Pranayama, Pratyahara, Dharana, and Samadhi Dhyna. Of the eight sections in the first five sections form the outer member (Bahir-yoga) of yoga or make your body fresh and healthy, because it contains about body movements contained in the teachings of yoga, while this part of the last three limbs form in the so-called intertine.